(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
This study aimed to know about the condition of the Gowa-Tallo Kingdom before Sultan Mahmud Karaeng Pattingalloang’s era such as the economy, knowledge, trading, and relation to the kingdoms or countries at that time. The second problem that this study aimed to know was the condition during Sultan Mahmud Karaeng Pattingalloang’s era that not like before his era there were improvements found in this study. This study used observation directly in the Museum of Karaeng Pattingalloang in Somba Opu, Gowa. The study used the descriptive qualitative method to ease the collected data into information that was easy to understand and so this study was appropriate to the results of this study found that before and during Sultan Mahmud Karaeng Pattingalloang’s era there were some specific differences such as the form of the kingdom, relation, knowledge, and economy are better or in stable condition, moreover at his era was the golden era of this Kingdom.